Detection of HO2 in an atmospheric pressure plasma jet using optical feedback cavity-enhanced absorption spectroscopy. (16th November 2016) - Gianella, Michele; Reuter, Stephan; Aguila, Ana Lawry; Ritchie, Grant A D; Helden, Jean-Pierre H van
Abstract: Cold non-equilibrium atmospheric pressure plasma jets are increasingly applied in material processing and plasma medicine. However, their small dimensions make diagnosing the fluxes of generated species a challenge. Here we report on the detection of the hydroperoxyl radical, HO2, in the effluent of a plasma jet by the use of optical feedback cavity-enhanced absorption spectroscopy. The spectrometer has a minimum detectable absorption coefficient α min of 2.25 × 10 − 10 cm −1 with a 100 second acquisition, equivalent to 5.5 × 10 12 cm − 3 of HO2 (under ideal conditions). Concentrations in the range of (3.1–7.8) × 10 13 cm −3 were inferred in the 4 mm wide effluent of the plasma jet.